Hubungan Antara Luas Lesi Foto Toraks dengan Hasil Pemeriksaan Sputum BTA Pasien Tuberculosis Paru Sebelum dan Sesudah Pengobatan di RS Ibnu Sina Makassar dan RS Balai Besar Kesehatan Paru Masyarakat Makassar - Putra, Muhammad Afief Batara; Latief , Shofiyah; Kidingallo, Yusuf; Syahril, Erlin; Sandy, Pither (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to find the relationship between the extent of chest X-ray lesions and the results of BTA sputum examinations in tuberculosis patients before and after treatment. This study uses a Cross Sectional approach. The data used to see the relationship between chest X-ray images and BTA sputum examinations were taken from the medical records of TB patients in 2021–2022 at Ibnu Sina Hospital and the Makassar Community Lung Health Center. Data analysis used bivariate analysis. Based on this study, it was concluded that there was a significant relationship between the extent of chest X-ray lesions and BTA sputum examinations before and after treatment at Ibnu Sina Hospital and the Makassar Community Lung Health Center.